Statement of Financial Accounting Standard (PSAK) No. 109 and Its Implementation in Several Zakat Management Organizations in Malang, East Java - Hasibuan, Henny Triyana (Faculty of Islamic Economics and Business, Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
Abstract Indonesian Accountant Association (IAI) has issued the statement of financial accounting standards No. 109 (PSAK No. 109) regarding zakat, infaq, sadaqah (ZIS). This research was conducted on several Zakat Management Organization (OPZ) in Malang, East Java. This research aims to analyze the consistency of the PSAK application in some OPZ in Malang in accordance with Statement of Financial Accounting Standards (PSAK) No. 109. As a result, this research finds that some OPZ in Malang do not prepare financial statements in accordance with PSAK 109. The financial statements of the OPZ is reported only in the form of income statements and distribution funds, while excluding such statements as financial position, changes in funds, changes in assets, cash flow and remarks to the financial statements. This research give a salient contribution of analyzing the implementation of zakat, infaq and sadaqah in Indonesia. KeywordsPSAK No.109, Indonesian Accountant Association (IAI), zakat, infaq, sadaqah